2014
DOI: 10.1007/s40519-014-0130-7
|View full text |Cite
|
Sign up to set email alerts
|

Eating behavior and perception of body shape in Japanese university students

Abstract: PurposeWe investigated the relationship between eating behavior measured by the Dutch Eating Behaviour Questionnaire (DEBQ) and perception of body shape, examining the current physical status and ‘ideal’ physical parameters in females and males.MethodsThe participants, 548 Japanese university students (age 19.2 ± 0.9 years, mean ± SD; 252 males, 296 females), completed a questionnaire which asked for their current physical status (e.g., weight and height), their ideal physical parameters, their perception of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 29 publications
2
19
0
5
Order By: Relevance
“…In alignment with previous research [6, 9, 21], the findings of the study showed that young women tend to overestimate their BMIs. However, body size perception accuracy was different across obesity categories; obese women with a BMI of 35–39.48 more accurately perceived their own body size than women with BMIs of 25–34.99, as Paul and colleagues addressed [5].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In alignment with previous research [6, 9, 21], the findings of the study showed that young women tend to overestimate their BMIs. However, body size perception accuracy was different across obesity categories; obese women with a BMI of 35–39.48 more accurately perceived their own body size than women with BMIs of 25–34.99, as Paul and colleagues addressed [5].…”
Section: Discussionsupporting
confidence: 89%
“…The parent study recruited 107 males and females who were between the ages of 18–29, overweight (BMI 25–29) or obese (BMI≥30), and exercised less than 90 minutes per week [19]. In this sub-study, we focused on young women, who are more vulnerable to body image issues and eating disorder than young men or older women [20, 21]. Further, individuals with a BMI of higher than 39.5 were excluded due to the limitations of the Body Image Assessment Tool-Body Dimension (BIAS-BD) (see more details in the measurement section).…”
Section: Methodsmentioning
confidence: 99%
“…Stigma in weight ultimately led to more negative physical and psychological health outcomes [ 21 23 ]. Recent studies found that stigma against weight (“anti-fat cultural context [ 21 ]”) was extremely high in South Korea [ 21 , 24 26 ] and Japan [ 27 , 28 ], but Chinese were more tolerant about overweight/obesity [ 9 , 24 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that gender differences regarding ideal body shape were related to eating behavior. 37 Prevalence of overweight and obesity among Japanese and Korean female university students was low. Body shape perception and ideal body shape were strongly influenced by socioeconomic factors.…”
Section: Open Journalmentioning
confidence: 99%
“…39 Collectively, studies have shown that misperceptions of body weight, height, BMI, and body shape of university students are subjected to a variety of influencing factors. Such factors include: gender, 35,36 age, 36 place of residence, 36 maternal education level, 36 eating behavior, 37 and socioeconomic factors. 38 Aspects of body weight, height, BMI, and body shape are all related to nutrition and lifestyle.…”
Section: Open Journalmentioning
confidence: 99%